Pyramid size control and morphology treatment for high-efficiency silicon heterojunction solar cells. (March 2019) - Tian, Xiaorang; Han, Peide; Zhao, Guanchao; Yang, Rong; Li, Liwei; Meng, Yuan; Guo, Ted
Abstract: This paper investigates the formation process of surface pyramid and etching characteristics during the texturing process of mono-crystalline silicon wafers. It is found that there is an etch rate transition point in alkaline anisotropic etching when 100 plane-dominated etch turns to 111 plane-dominated etch, and the pyramid size has a strong linear correlation with the etch amount at the transition point. Several techniques were developed to control the pyramid size by monitoring and adjusting the etching amount. A wide range of average pyramid sizes were successfully achieved, from 0.5 to 12 μ m. The experiments of the pyramid size on the light reflectance, the minority carrier lifetime (MCLT), and the performance of silicon heterojunction (SHJ) solar cells were carried out and analyzed. A desirable range of pyramid sizes was empirically determined by our investigation. In order to reduce the density states on the texturing surface, the wet-chemical smoothing treatment was also investigated. The smoothing treatment improves the passivation quality and the performance of the solar cells. Through pyramid size control and morphology treatment, together with the amorphous silicon (a-Si:H) deposition improvement, and electrode optimization, high performance of SHJ solar cells has been achieved, up to conversion efficiency 23.6%.